2008
DOI: 10.1007/s00397-007-0245-0
|View full text |Cite
|
Sign up to set email alerts
|

Gradient and vorticity banding

Abstract: "Banded structures" of macroscopic dimensions can be induced by simple shear flow in many different types of soft matter systems. Depending on whether these bands extend along the gradient or vorticity direction, the banding transition is referred to as "gradient banding" or "vorticity banding," respectively. The main features of gradient banding can be understood on the basis of a relatively simple constitutive equation. This minimal model for gradient banding will be discussed in some detail, and its predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(148 citation statements)
references
References 137 publications
(210 reference statements)
6
141
1
Order By: Relevance
“…6). This fact calls for a re-evaluation of experimental situations where the so-called 'vorticity banding' was observed [88][89][90][91][92][93]. Note moreover that the 'non-monotonic shear-thickening flow curve' underlying vorticity banding could be simply due to the emergence of secondary flows responsible for the increased resistance to flow.…”
Section: Effects Of the Salt Concentrationmentioning
confidence: 99%
“…6). This fact calls for a re-evaluation of experimental situations where the so-called 'vorticity banding' was observed [88][89][90][91][92][93]. Note moreover that the 'non-monotonic shear-thickening flow curve' underlying vorticity banding could be simply due to the emergence of secondary flows responsible for the increased resistance to flow.…”
Section: Effects Of the Salt Concentrationmentioning
confidence: 99%
“…It appears that the entanglements of polymeric chains are at the origin of the strong shear thinning behavior, which is necessary for gradient banding. 1 On the other hand, in recent experimental work with entangled synthetic polymers shear banding was not observed, but instead interfacial slip was suggested as the origin of strain loss. 10,11 Gradient banding has also been found in glassy starlike polymers.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to advances in theoretical understanding as well as experimental instrumentation. [1][2][3][4] In particular, a number of experimental studies of polymeric systems have revealed the occurrence of shear banding along the gradient direction in such systems. For example, experiments on entangled DNA solutions 5,6 and solutions of synthetic polymers [7][8][9] show pronounced gradientbanding velocity profiles.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, this helicopter rotation might be expected as well for colloidal rods systems in the proximity of a wall. It can also be speculated that for confined dense systems, clusters of rods undergoing helicopter oscillations close to a wall would separate from each other in regions perpendicular to the wall, which could be related to the still unclear phenomena of vorticity-band formation [23].…”
mentioning
confidence: 99%